2021
DOI: 10.3390/ijms22020617
|View full text |Cite
|
Sign up to set email alerts
|

The Odd Couple(s): An Overview of Beta-Lactam Antibiotics Bearing More Than One Pharmacophoric Group

Abstract: β-lactam antibiotics are among the most important and widely used antimicrobials worldwide and are comprised of a large family of compounds, obtained by chemical modifications of the common scaffolds. Usually these modifications include the addition of active groups, but less frequently, molecules were synthesized in which either two β-lactam rings were joined to create a single bifunctional compound, or the azetidinone ring was joined to another antibiotic scaffold or another molecule with a different activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 137 publications
1
24
0
Order By: Relevance
“…Next, biochemical studies with a blaC knockout strain suggested that BlaC activity was largely (although perhaps not exclusively) responsible for Pyr release. Finally, microbiological evaluation of the blaC knockout demonstrated increased susceptibility to the Pyr conjugate against replicating organisms and similar to WT activity under non-replicating conditions; potentiation of BLs against Mtb ΔblaC under actively replicating conditions has been demonstrated previously and is likely due to increased inhibition of PBPs, while the retained activity against non-replicating Mtb (for which PBP inhibition is not toxic) suggests the possibility of an alternative release mechanism independent of BLase or PBP activity. , A more expansive study recently reported by the authors, in collaboration with a large number of research organizations, identified additional Pyr cephalosporins with antitubercular activity, further validating this approach and adding to the growing body of evidence supporting BLs as new TB therapeutics. , These recent reports, as well as a few other recent papers exploring BLase fragmentation with fluoroquinolone, phenazine, and pyrazinoic acid conjugates, demonstrate the continued promise of this approach in circumventing limitations such as off-target effects or resistance mechanisms to repurpose known antibiotics for new antibacterial applications (Figure D–F). Many more examples of BL–antibiotic conjugates can be found in several recent reviews on this subject. …”
Section: Antibiotics: Lactam Conjugates As Pro- and Co-drugssupporting
confidence: 59%
“…Next, biochemical studies with a blaC knockout strain suggested that BlaC activity was largely (although perhaps not exclusively) responsible for Pyr release. Finally, microbiological evaluation of the blaC knockout demonstrated increased susceptibility to the Pyr conjugate against replicating organisms and similar to WT activity under non-replicating conditions; potentiation of BLs against Mtb ΔblaC under actively replicating conditions has been demonstrated previously and is likely due to increased inhibition of PBPs, while the retained activity against non-replicating Mtb (for which PBP inhibition is not toxic) suggests the possibility of an alternative release mechanism independent of BLase or PBP activity. , A more expansive study recently reported by the authors, in collaboration with a large number of research organizations, identified additional Pyr cephalosporins with antitubercular activity, further validating this approach and adding to the growing body of evidence supporting BLs as new TB therapeutics. , These recent reports, as well as a few other recent papers exploring BLase fragmentation with fluoroquinolone, phenazine, and pyrazinoic acid conjugates, demonstrate the continued promise of this approach in circumventing limitations such as off-target effects or resistance mechanisms to repurpose known antibiotics for new antibacterial applications (Figure D–F). Many more examples of BL–antibiotic conjugates can be found in several recent reviews on this subject. …”
Section: Antibiotics: Lactam Conjugates As Pro- and Co-drugssupporting
confidence: 59%
“…Column chromatography was performed using Merck silica gel 60 of mesh size 0.040−0.063 mm. 1 H and 13 C NMR spectra were recorded using Bruker DPX 600 at 600 MHz. Mass spectra were recorded with a Thermo Fisher DFS Magnetic Sector GC-HRMS spectrometer.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Deriving novel bis-β-lactams-based unsaturated macrocycles (Figure 1) has received considerable attention with notable impact not only in organic synthesis but also in other research areas such as medicine, pharmaceutical, and supramolecular chemistry. 1 Sequential organic transformations based on (i) formation of diimine substrates, (ii) Staudinger [2 + 2] ketene−imine cycloaddition, and (iii) ring-closing metathesis (Figure 1) have been typically exploited as suitable synthetic procedures for the construction of new bis-2-azetidinone-based azacrown ethers with an unparallel opportunity for researchers to explore their utilities as feasible bioactive materials, owing to the promising biological potentials including antimicrobial, 2,3 antimalarial, 4,5 and anticancer activities 6,7 of the β-lactam site.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four specific classes of beta-lactams are used in clinical practice, including penicillins, cephalosporins, carbapenems, and monobactams. All beta-lactam classes consist of a four-member ring, referred to as the beta-lactam ring or azetidinone [6]. Monobactams are monocyclic, while the remaining classes are fused to a five-or six-member ring.…”
Section: Introductionmentioning
confidence: 99%